Strategies to Improve Sustainable Competitive Advantage in the Halal Industry Through Knowledge Sharing: HR Perspective - Taufiq Rahmat; Eeng Ahman; Diah Apriliani (Equity: Jurnal Ekonomi, 2024)
The halal industry in Indonesia faces significant challenges in establishing a sustainable competitive advantage (SCA) in an increasingly competitive global market. One key factor that could support this advantage is the adoption of Green Human Resource Management (GHRM) practices and the promotion of green knowledge sharing. This study investigates the relationship between GHRM practices, green knowledge sharing, and the achievement of SCA within the Indonesian halal industry. Employing a systematic literature review (SLR) methodology, the study utilizes the Resource-Based View (RBV) theory to analyze relevant literature. The search was conducted using Scopus and Google Scholar databases, focusing on GHRM, knowledge sharing, and competitive advantage. The findings indicate that GHRM positively influences SCA, with green knowledge sharing acting as both a mediator and moderator that strengthens this effect. Additionally, organizational citizenship behavior (OCB), driven by green leadership, further contributes to the achievement of SCA. This research offers theoretical insights into the application of RBV within the halal industry and underscores the significance of green knowledge sharing and OCB in fostering sustainable competitive advantage. The practical implication of these findings highlights the importance of implementing effective GHRM practices and cultivating a green knowledge-sharing culture to enhance sustainability in the halal sector. The study's limitation lies in its reliance on existing literature, without empirical analysis in the field.